Homes integrated as an institution (total) in the support system for adults with deep intellectual disability – introduction to consideration - Gawlik, Ewa (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
The article discusses the subject of housing for people with more severe intellectual disability – as one of the forms of support. The integrated-community flat constitutes an alternative institutional form of support for persons with more severe intellectual disability. The symbolic interactionism theory was extremely helpful in preliminary deliberations and the discussed integrated-community flats were based on the conception of total institutions. Therefore, the following questions were asked: What characteristics of a total institution does the integrated-community flat have? Can the integrated-community flat be described as having characteristics of a total institution? A qualitative case study with participant observation was used for this purpose.